Reproductive performance and disorders in mares - Purohit, G N; Sharma, B S; Gupta, K A (The Indian Journal of Animal Sciences, 2012)
Reproductive performance and disorders were studied for thoroughbred mares from 1993 to 1996. The overall mean estrus cycle length (EL) and estrus period (EP) were 14.98±1.12 and 6.04±0.248 days. Both EL and EP did not vary between the years, but differed significantly between the months (P<0.05). The overall mean coverings required per foal born were 9.87. Maximum foalings occurred in April (19) followed by March (18), February (14), May (11) and June (2), 64.61 % of the foalings occurring at night to mid-night, 21.53% at early morning and only 6.15% during day hours. Mares evidenced foal heat with an interval of 7. 78±0. 72 days after foaling in 56.92% cases. The abortion per cent was 13.15, 40% of the total abortions being due to twinning. The sex ratio was 43.07% male births. Reproductive disorders were uncommon, there were 4.61, 0.71, 4.28 and 3.57% cases of placental retention, vaginitis, pneumovagina and anestrus.